Investigation on changes in gamma prime precipitate on varying surface locations of IN738 engine turbine blade - Hamizol, M.S. (Universiti Malaysia Pahang, 2016)
Changes in microstructure of a service exposed turbine engine blade have been found to affect the elemental composition and the performance because the existing bond structures, as well as the phase distribution of the blade material, deteriorates as a consequence of the changes. As such, this systematic internal deformation, which can expedite the creep and crack formation, has been a source of concern for the industry. Besides, failure in understanding these microstructural changes can lead to disregard of necessary and vital preventive measures. Hence, the present study investigates a turbine engine blade with estimated operating hours of 52000 at ±720°C to examine the changes that occur in the microstructure of blade material from different points of the blade. For that purpose, scanning electron microscopy (SEM) was used to analyse the grain boundary formation and the gamma prime precipitates. In fact, the presence of the gamma prime phase in the microstructure had been proven to be a major contributing factor that enhanced nucleation and propagation creep. Other than that, the varied locations on the blade were examined and compared to determine the critical points that affected the performance of blade during operation using an electric discharge machine (EDM). Furthermore, the development of gamma prime precipitates had been rather obvious in the equilibrium phase than that in the solid phase due to temperature variation. On top of that, the transformation in the pressure surface location displayed more intensity than the suction surface location, in which limited carbides (MC) was observed in the suction surface location, whereas the grain boundary growth had been sporadic. However, continuous gamma prime precipitate was discovered in the pressure surface location. Hence, this study infers that changes that take place in the microstructure of the blade do not solely depend on the hours exposed or the intensity of subjected pressure, but such changes are deemed to occur due to a number of other essential aspects, for instance, material bulk properties, alloy constituents, loss of surface coherence, coarsening, and condition of operation. © Universiti Malaysia Pahang.